Comparison of sodium sulphate deposition rate models based on operational factors influencing hot corrosion damage in aero-engines - Pontika, Evangelia; Laskaridis, Panagiotis; Nikolaidis, Theoklis; Koster, Max (American Society of Mechanical Engineers (ASME), 2021)
Hot corrosion is defined as the accelerated oxidation/sulphidation in the presence of alkali metal molten salts. It is a form of chemical attack that causes good metal loss. Current lifing models in aircraft engines focus on creep, fatigue and oxidation while hot corrosion damage has been overlooked as being of secondary importance. However, the absence of hot corrosion lifing models for aircraft engines often leads to unexpected and unexplained hot corrosion findings by aircraft engine operators and Maintenance, Repair and Overhaul (MRO) providers during inspections. Although hot corrosion does not cause failure on its own, the interaction with other damage mechanisms can reduce component life significantly, consequently, there is a requirement for including hot corrosion in the damage prediction process of aircraft engines. In both theoretical and experimental studies in literature, deposition of molten salts is identified as one of the primary conditions for hot corrosion to occur and an increased amount of deposited liquid salts accelerates the attack. Currently, most hot corrosion studies are limited to experimental testing of superalloys which are pre-coated with a controlled layer of salts. Such experimental studies are disconnected from gas turbine operating conditions during service. The present paper analyses two deposition rate models applicable to gas turbine operating conditions using Design of Experiments. Design space exploration is presented by taking into account gas turbine operating parameters which vary during a flight as well as temperature ranges where hot corrosion can occur. Analysis of variance is presented for 6 input parameters using Box-Behnken 3-level factorial design. Results from the Analysis of Variance indicate that the deposition rate models are sensitive to pressure and salt concentration in the gas flow. Finally, the saturation point of sodium sulphate has been investigated within the operating range of gas turbine and it was found that it can vary significantly under different conditions.
Keywords: hot corrosion; deposition rate model; design of experiments